Comparison of problem/case-based learning with lecture-based learning in the clinical teaching of ophthalmology - Wu, Changfan; Chen, Anran; Yu, Yan; Zhao, Haifeng; Hu, Lingfei; Jin, Huixiang (International Journal Of Community Medicine And Public Health, 2019)
Background: Few researches have focused on the effectiveness of problem/case-based learning (PCBL) method in clinical teaching of ophthalmology among undergraduate students and their evaluation feedbacks to this method. Knowledge of current different approaches of teaching clinical ophthalmology might help to achieve better learning effect. So, our aim was to compare problem/case-based learning (PCBL) with lecture-based learning (LBL) in the education of medical students and investigate the student perceptions of teaching ophthalmology by the PCBL approach. Methods: Two classes of fourth-year medical students were divided into two groups by class-based randomly and were taught the ocular trauma course. A total of 76 students studied in lectures and 87 students learned in a problem/case -based learning discussion session. Five questions were designed on ocular trauma in the final examination to evaluate the effectiveness of these two teaching methods. Students with the PCBL perceptions were collected to analyse the effectiveness of the PCBL. Results: Comparing with LBL, a significantly higher overall examination score occurred in the PCBL group. Most students in the PCBL class agreed that PCBL performed better in improving their understanding of the subject materials, promoting learning motivation, and enhancing the communication skill and clinical thinking method. Conclusions: The PCBL is an effective approach to assist students in understanding the clinical diagnosis and treatment of ocular diseases. This teaching method helps students increase the motivation of improving learning and problem-handling skills.